Preparation method of high-melt high-fluidity acrylate copolymer

By grafting stearic acid on hydroxyacrylate and synthesizing high-melt high-flow acrylate copolymer with modified hydroxyacrylate, methyl methacrylate and styrene, its low-temperature brittleness and high-temperature change are solved The problem of stickiness improves fluidity and processing performance.

CN119505072AInactive Publication Date: 2025-02-25SHANDONG HETIANXIA NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510051892.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The problems of acrylate copolymer becoming brittle at low temperatures and sticky at high temperatures lead to poor processing fluidity and reducing production efficiency and product quality.

Method used

Stearic acid is grafted on the hydroxyacrylate through the esterification reaction, and the modified hydroxyacrylate is used as the soft monomer, methyl methacrylate and styrene are used as the hard monomer, and silane coupling agent is used as the crosslinking synthesis of high melt high flow acrylate copolymer.

Benefits of technology

The melt flowability and processing properties of the acrylate copolymer are improved, the weather resistance, heat resistance and mechanical strength are enhanced, and the low-temperature toughness and stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505072A_ABST
    Figure CN119505072A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of acrylate copolymers, in particular to a preparation method of a high-melt and high-fluidity acrylate copolymer. The preparation method of the high-melt and high-fluidity acrylate copolymer comprises the following specific steps: firstly, mixing an emulsifier with water to obtain an emulsified solution, then reacting hydroxyl acrylate with stearic acid, grafting a long-chain branch, then pre-emulsifying reactants by using the emulsified solution, and finally reacting the pre-emulsified reactants, so as to obtain the high-melt and high-fluidity acrylate copolymer. Through the modification of hydroxyl acrylate, the melt flowability and impact strength of the acrylate copolymer are improved; polysiloxane is introduced in the preparation process, so that the melt flowability and the impact strength of the acrylate copolymer are further improved; in addition, a non-ionic surface active agent is introduced into the polysiloxane modified acrylate copolymer by adopting a swelling-deswelling method, so that the mechanical property of the acrylate copolymer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of acrylic ester copolymers, and in particular to a method for preparing a high-melt high-fluidity acrylic ester copolymer. Background Art

[0002] Acrylate copolymer is a polymer produced by the copolymerization reaction of acrylate monomers and other comonomers. It is an important polymer material with excellent transparency, weather resistance, adhesion and film-forming properties, and is used in plastics, coatings, adhesives and other fields.

[0003] However, acrylate copolymers also have defects such as becoming brittle at low temperatures and having high viscosity at high temperatures, which make their fluidity poor during processing, reduce production efficiency and product quality, and limit their application and use value. In recent years, with the continuous development of polymerization technology and people's attention to environmental protection and safety, the modification of high melt and high fluidity of acrylate copolymers has attracted people's attention.

[0004] At present, there are two main methods for obtaining high-melt and high-fluidity acrylic copolymers: physical blending and chemical modification. The physical blending method is to blend the modified material with the acrylic copolymer in a certain proportion under certain temperature and shear conditions, so that the modified material is dispersed in the acrylic copolymer. However, this method does not truly form the modified material and the acrylic copolymer into a whole, so the stability of the modified acrylic copolymer is poor; the chemical modification method is to connect the active functional groups of the modified material with the acrylic monomer through copolymerization, polycondensation and other reactions. This method forms the modified material and the acrylic copolymer into a whole through chemical bonds, and the stability after modification is good.

[0005] A Chinese patent application document with publication number CN102464784A discloses a method for synthesizing an organosilicon-modified acrylate copolymer. The method comprises first synthesizing an organosilicon seed emulsion, and then grafting and coating the copolymer with an acrylate monomer to prepare a polyorganosiloxane-polyacrylate composite material having the characteristics of high strength and good toughness. However, during the grafting and coating, the organosilicon containing double bonds has basically reacted, and then the acrylate monomer is grafted to form a composite material with polyorganosiloxane on the inside and polyacrylate on the outside. The interaction force between the inside and the outside is relatively weak, and when the composite material is in a molten state, it may cause instability of the composite material and affect the material performance. Summary of the invention

[0006] In order to alleviate the phenomenon that acrylate copolymers become brittle at low temperatures and become sticky at high temperatures and to improve the melt fluidity and processing performance of acrylate copolymers, the present application provides a method for preparing high-melt and high-fluidity acrylate copolymers.

[0007] A method for preparing a high-melt high-fluidity acrylic copolymer comprises the following steps: S1: Mixing softened water and an emulsifier, stirring, heating and emulsifying to obtain an emulsified solution; S2: reacting hydroxy acrylate, stearic acid and catalyst at 130-160°C for 3-5h, cooling to 60-80°C after the reaction, washing and vacuum drying the product to obtain modified hydroxy acrylate; S3: mixing and stirring the emulsified solution and the modified hydroxy acrylate to obtain a pre-emulsion A; mixing and stirring the emulsified solution, methyl methacrylate, styrene and a silane coupling agent to obtain a pre-emulsion B; S4: Sodium bicarbonate, softened water and pre-emulsion A are stirred evenly, heated to 80°C, an initiator is added, and after reacting for 0.5-1h, pre-emulsion A and the initiator are slowly added, and the mixture is kept warm for 1-3h, pre-emulsion B and the initiator are slowly added, and the mixture is kept warm for 1-3h to obtain a mixed emulsion; S5: Cool down with circulating water, adjust the pH to 8-9, let stand and dry.

[0008] In the above technical scheme, first, stearic acid is grafted on hydroxy acrylate through esterification reaction, then the reactants are pre-emulsified, and finally the modified hydroxy acrylate is used as a soft monomer, methyl methacrylate and styrene are used as hard monomers, and silane coupling agent is used as a crosslinking agent to synthesize a high-melt high-fluidity acrylate copolymer. On the one hand, the acrylate copolymer is a relatively soft hydroxy acrylate polymer as the core, and a copolymer of methyl methacrylate and styrene with greater hardness is used as the shell, and a silane coupling agent is added to further improve the strength of the shell and the connection strength between the shell and the core. This soft core makes the acrylate copolymer have better fluidity in the molten state; the strong connection between the hard shell and the core shell improves the weather resistance, heat resistance and mechanical strength of the acrylate copolymer; and at low temperatures, when the high-melt high-fluidity acrylate copolymer is impacted, the hard shell can withstand stress, and as a stress concentration point, the soft core can evacuate stress and reduce the damage of the acrylate copolymer material, so the toughness of the acrylate copolymer material at low temperatures can be improved, and the low-temperature resistance of the acrylate copolymer material can be improved.

[0009] On the other hand, the reaction of hydroxyacrylate with stearic acid and the grafting of flexible long side chains on hydroxyacrylate can increase the distance between hydroxyacrylate polymer molecules and reduce the mutual entanglement density of hydroxyacrylate polymer molecules, thereby making the hydroxyacrylate polymer have a larger free volume and a lower viscosity; moreover, the longer flexible molecular chains can also shield the molecular chains of hydroxyacrylate polymers, effectively reducing the friction between the molecular chains, thereby increasing fluidity.

[0010] Preferably, the mixed emulsion in step S4 is modified by a method comprising the following steps: In the organosiloxane solution, add hydrochloric acid dropwise while stirring, adjust the solution pH to 4-5, react for 3-5 hours, add emulsifier, acrylate monomer and mixed emulsion, stir evenly, heat to 75-85°C, slowly add initiator, adjust the pH to 8-9, and keep warm for 1-3 hours.

[0011] By adopting the above technical scheme, during the synthesis process of polysiloxane, acrylic acid ester undergoes polymerization reaction at the same time. After the reaction is completed, the acrylic acid ester copolymer is coated with a soft and smooth polysiloxane polymer. In addition, the polysiloxane and the polyacrylate are interspersed together, which increases the interaction force between the polysiloxane and the acrylic acid ester copolymer and improves the compatibility between the polysiloxane and the acrylic acid ester copolymer. After the acrylic acid ester copolymer is melted, the softness and smoothness of the polysiloxane can reduce the friction between the copolymer molecules and the friction between the copolymer molecules and the container wall. At the same time, the polysiloxane is not easy to separate from the acrylic acid ester copolymer, which improves the melt stability, thereby further improving the fluidity in the molten state.

[0012] Preferably, the emulsifier is one or more of fatty alcohol polyoxyethylene ether sodium sulfate, nonylphenol polyoxyethylene ether and sodium dodecyl sulfate.

[0013] Preferably, in step S2, the hydroxyacrylate is one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate; the catalyst is one of nano-silicon dioxide, nano-alumina and nano-zirconium oxide; the mass ratio of the hydroxyacrylate, stearic acid and catalyst is 100: (100-250): (0.8-2.4).

[0014] Preferably, in step S3, the silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane; the mass ratio of the modified hydroxy acrylate, methyl methacrylate, styrene and silane coupling agent is 100: (100-200): (50-80): (5-10).

[0015] Preferably, in step S4, the initiator is potassium persulfate or ammonium persulfate; and the ratio of the total mass of the pre-emulsion A and the pre-emulsion B to the total mass of the initiator used is 100:(1.2-2.5).

[0016] Preferably, the organosiloxane is one or more of methyltrimethoxysilane, methyltriethoxysilane and hexamethyldisiloxane; and the mass fraction of the organosiloxane solution is 20%.

[0017] Preferably, the mass ratio of the acrylate monomer, the organosiloxane, the mixed emulsion and the initiator is 1:(5-10):(10-30):(0.01-0.03).

[0018] Further preferably, the obtained high melt high fluidity acrylic ester copolymer is modified by a method comprising the following steps: Dissolve the nonionic surfactant in toluene to prepare a solution with a mass fraction of 1%-5%, add the high-melt high-fluidity acrylic copolymer, swell for 5-15 minutes, take out, wash and vacuum dry.

[0019] In the above technical scheme, after the polysiloxane-modified acrylate copolymer is swollen, a small amount of non-ionic surfactant is added. The non-ionic surfactant is a triblock polymer with hydrophilic segments at both ends and a hydrophobic segment in the middle. The hydrophobic segment can be "planted" inside the polysiloxane, and the hydrophilic segment is attached to the surface and outside the polysiloxane surface, thereby increasing the hydrophilicity of the polysiloxane-modified acrylate copolymer and improving the interaction force, thereby improving the stability of the acrylate copolymer material; at the same time, the embedding of the surfactant molecular chain also reduces the mutual cross-linking entanglement between the polysiloxanes, which is beneficial to reducing the viscosity in the molten state and improving the melt fluidity.

[0020] Preferably, the nonionic surfactant is one or more of poloxamer F188, poloxamer F127 and poloxamer F68.

[0021] The above technical solution of the present application includes at least the following beneficial effects: 1. The present application modifies hydroxy acrylate, and the soft long chain branches reduce the chain entanglement density between polymer molecules, increase the free volume, reduce the viscosity in the molten state, and improve the melt fluidity.

[0022] 2. The present application synthesizes polysiloxane and polyacrylate simultaneously, so that the molecular chains are interlaced, which not only improves the compatibility of polysiloxane and acrylate copolymer, but also improves the strength and melt fluidity.

[0023] 3. The present application utilizes the interaction between the hydrophobic segment of the nonionic surfactant and the polysiloxane, and the hydrophilic segment is exposed to the outside, thereby improving the interaction and compatibility between the acrylate copolymers, improving the melt fluidity, and improving the stability of the acrylate copolymer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the trend graph of shear viscosity changing with shear rate; Figure 2 is the melt flow rate of the high melt high fluidity acrylate copolymer; Figure 3 Tensile strength and impact strength of high melt high flow acrylic copolymer. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with embodiments.

[0026] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0027] Example Example 1 The preparation method of the high-melt high-fluidity acrylic ester copolymer of this embodiment comprises the following steps: S1: Add 100 g of softened water, 6 g of sodium fatty alcohol polyoxyethylene ether sulfate, and 4 g of sodium dodecyl sulfate into a reaction kettle, start stirring in the kettle, heat with steam to 40° C., emulsify for 1.5 h to completely dissolve the emulsifier, and obtain an emulsified solution; S2: Weigh 100 g of hydroxyethyl methacrylate, 100 g of stearic acid and 0.8 g of nano zirconium oxide, place in a three-necked flask, heat until melted, start magnetic stirring, react at 130° C. for 5 h, cool to 60° C. after the reaction, wash the product with deionized water, and vacuum dry to obtain modified hydroxyethyl methacrylate; S3: Weigh 35 g of the emulsified solution and 100 g of modified hydroxyethyl methacrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 100 g of methyl methacrylate, 50 g of styrene, and 5 g of γ-methacryloxypropyltrimethoxysilane, stir for 30 min, and obtain pre-emulsion B; S4: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 1 g of potassium persulfate, react for 0.5 h, slowly add the remaining pre-emulsion A and 0.8 g of potassium persulfate, keep warm for 1 h, slowly add pre-emulsion B and 1.2 g of potassium persulfate, keep warm for 3 h, and obtain a mixed emulsion; S5: Cool down with circulating water, repeat 3 times, adjust the pH to 8, let it stand for 1 hour, and then dry.

[0028] Example 2 The preparation method of the high-melt high-fluidity acrylic ester copolymer of this embodiment comprises the following steps: S1: Add 100 g of softened water, 6 g of nonylphenol polyoxyethylene ether, and 4 g of sodium dodecyl sulfate into a reaction kettle, start stirring in the kettle, heat to 50° C. with steam, and emulsify for 0.5 h to completely dissolve the emulsifier to obtain an emulsified solution; S2: Weigh 100 g of hydroxyethyl acrylate, 250 g of stearic acid and 2.4 g of nano-silicon oxide, place in a three-necked flask, heat until melted, start magnetic stirring, react at 160° C. for 3 h, cool to 80° C. after the reaction, wash the product with deionized water, and vacuum dry to obtain modified hydroxyethyl acrylate; S3: Weigh 35 g of the emulsified solution and 100 g of modified hydroxyethyl acrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 100 g of methyl methacrylate, 50 g of styrene and 5 g of vinyl triethoxysilane, stir for 30 min, and obtain pre-emulsion B; S4: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 1 g of potassium persulfate, react for 1 hour, slowly add the remaining pre-emulsion A and 0.8 g of potassium persulfate, keep warm for 3 hours, slowly add pre-emulsion B and 1.2 g of potassium persulfate, keep warm for 1 hour, and obtain a mixed emulsion; S5: Cool down with circulating water, repeat 3 times, adjust the pH to 9, let it stand for 3 hours, and then dry.

[0029] Example 3 The preparation method of the high-melt high-fluidity acrylic ester copolymer of this embodiment comprises the following steps: S1: Add 100 g of softened water, 6 g of nonylphenol polyoxyethylene ether, and 4 g of sodium vinyl sulfonate of fatty alcohol ether into a reaction kettle, start stirring in the kettle, heat to 45° C. with steam, and emulsify for 1 h to completely dissolve the emulsifier to obtain an emulsified solution; S2: Weigh 100 g of hydroxypropyl acrylate, 150 g of stearic acid and 1.5 g of nano-alumina, place in a three-necked flask, heat until melted, start magnetic stirring, react at 150° C. for 3 h, cool to 80° C. after the reaction, wash the product with deionized water, and vacuum dry to obtain modified hydroxypropyl acrylate; S3: Weigh 35 g of the emulsified solution and 100 g of modified hydroxypropyl methacrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 100 g of methyl methacrylate, 50 g of styrene and 5 g of vinyltrimethoxysilane, stir for 30 min, and obtain pre-emulsion B; S4: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 1 g of ammonium persulfate, react for 0.5 h, slowly add the remaining pre-emulsion A and 0.8 g of ammonium persulfate, keep warm for 2 h, slowly add pre-emulsion B and 1.2 g of ammonium persulfate, keep warm for 2 h, and obtain a mixed emulsion; S5: Cool down with circulating water, repeat 3 times, adjust the pH to 8.5, let it stand for 2 hours, and then dry.

[0030] Example 4 The method for preparing the high-melt high-fluidity acrylic copolymer of this embodiment is different from that of Example 3 in that: S3: Weigh 35 g of the emulsified solution and 100 g of modified hydroxypropyl methacrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 200 g of methyl methacrylate, 80 g of styrene, and 10 g of vinyltrimethoxysilane, stir for 30 min, and obtain pre-emulsion B; S4: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 2 g of ammonium persulfate, react for 0.5 h, slowly add the remaining pre-emulsion A and 3 g of ammonium persulfate, keep warm for 2 h, slowly add pre-emulsion B and 4.5 g of ammonium persulfate, keep warm for 2 h, and obtain a mixed emulsion; The remaining steps are the same as those in Example 3.

[0031] Example 5 The method for preparing the high-melt high-fluidity acrylic copolymer of this embodiment is different from that of Example 3 in that: S3: Weigh 35 g of the emulsified solution and 100 g of modified hydroxypropyl methacrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 150 g of methyl methacrylate, 50 g of styrene and 8 g of vinyltrimethoxysilane, stir for 30 min, and obtain pre-emulsion B; S4: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 1 g of ammonium persulfate, react for 0.5 h, slowly add the remaining pre-emulsion A and 1.5 g of ammonium persulfate, keep warm for 2 h, slowly add pre-emulsion B and 2.5 g of ammonium persulfate, keep warm for 2 h, and obtain a mixed emulsion; The remaining steps are the same as those in Example 3.

[0032] Example 6 The method for preparing the high-melt high-fluidity acrylic ester copolymer of this embodiment is different from that of Example 5 in that: In step S4, the mixed emulsion is modified by a method comprising the following steps: Weigh 50g of methyltrimethoxysilane and dissolve it in deionized water to make a 20% aqueous solution. Add dilute hydrochloric acid while stirring, adjust the pH value to 4, react for 3h, add 3g of fatty alcohol polyoxyethylene ether sodium sulfate, 10g of acrylate monomer and 100g of mixed emulsion, stir evenly, heat to 75℃, slowly add 0.1g of ammonium persulfate, adjust the pH value to 8, and keep warm for 1h. The remaining steps are the same as those in Example 5.

[0033] Example 7 The method for preparing the high-melt high-fluidity acrylic ester copolymer of this embodiment is different from that of Example 5 in that: In step S4, the mixed emulsion is modified by a method comprising the following steps: Weigh 75g of methyltriethoxysilane and dissolve it in deionized water to make a 20% aqueous solution. Add dilute hydrochloric acid while stirring, adjust the pH value to 5, react for 5h, add 3g of sodium sulfate of fatty alcohol polyoxyethylene ether, 10g of acrylate monomer and 300g of mixed emulsion, stir evenly, heat to 85°C, slowly add 0.3g of ammonium persulfate, adjust the pH value to 9, and keep warm for 3h. The remaining steps are the same as those in Example 5.

[0034] Example 8 The method for preparing the high-melt high-fluidity acrylic ester copolymer of this embodiment is different from that of Example 5 in that: In step S4, the mixed emulsion is modified by a method comprising the following steps: Weigh 100g of hexamethyldisiloxane and dissolve it in deionized water to make a 20% aqueous solution. Add dilute hydrochloric acid while stirring, adjust the pH value to 5, react for 5h, add 3g of sodium sulfate of fatty alcohol polyoxyethylene ether, 10g of acrylate monomer and 300g of mixed emulsion, stir evenly, heat to 85℃, slowly add 0.3g of ammonium persulfate, adjust the pH value to 9, and keep warm for 3h. The remaining steps are the same as those in Example 5.

[0035] Example 9 The preparation method of the high-melt high-fluidity acrylate copolymer of this embodiment is different from that of Embodiment 8 in that the obtained high-melt high-fluidity acrylate copolymer is modified by a method comprising the following steps: The surfactant poloxamer F127 is dissolved in toluene to prepare a solution with a mass fraction of 1%, and a high-melt high-fluidity acrylate copolymer is added to swell for 5 minutes. After taking out, the solution is washed and vacuum dried. The remaining steps are the same as those in Example 8.

[0036] Example 10 The preparation method of the high-melt high-fluidity acrylate copolymer of this embodiment is different from that of Embodiment 8 in that the obtained high-melt high-fluidity acrylate copolymer is modified by a method comprising the following steps: The surfactant poloxamer F68 is dissolved in toluene to prepare a 5% solution, and a high-melt high-fluidity acrylate copolymer is added to swell for 15 minutes. After taking out, the solution is washed and vacuum dried. The remaining steps are the same as those in Example 8.

[0037] Comparative Example Comparative Example 1 The preparation method of the high-melt high-fluidity acrylic ester copolymer of this comparative example comprises the following steps: S1: Add 100 g of softened water, 6 g of sodium fatty alcohol polyoxyethylene ether sulfate, and 4 g of sodium dodecyl sulfate into a reaction kettle, start stirring in the kettle, heat with steam to 40° C., emulsify for 1.5 h to completely dissolve the emulsifier, and obtain an emulsified solution; S2: Add 100 g of hydroxyethyl methacrylate, 100 g of methyl methacrylate, 50 g of styrene and 5 g of γ-methacryloxypropyltrimethoxysilane to the above emulsified solution and stir for 30 min to obtain a pre-emulsion; S3: In a reaction kettle equipped with a stirrer, 0.8 g of sodium bicarbonate, 40 g of softened water and the above pre-emulsion were added, heated to 80° C., 3 g of potassium persulfate was added, and the mixture was kept warm for 3 h to obtain a mixed emulsion; S4: Cool down with circulating water, repeat 3 times, adjust the pH to 8, let it stand for 1 hour, and then dry.

[0038] Comparative Example 2 The preparation method of the high-melt high-fluidity acrylic ester copolymer of this comparative example comprises the following steps: S1: Add 100 g of softened water, 6 g of sodium fatty alcohol polyoxyethylene ether sulfate, and 4 g of sodium dodecyl sulfate into a reaction kettle, start stirring in the kettle, heat with steam to 40° C., emulsify for 1.5 h to completely dissolve the emulsifier, and obtain an emulsified solution; S2: Weigh 45 g of the emulsified solution and 100 g of hydroxyethyl methacrylate, stir for 30 min, and obtain pre-emulsion A; weigh 75 g of the emulsified solution, 200 g of methyl methacrylate, 50 g of styrene, and 5 g of γ-methacryloxypropyltrimethoxysilane, stir for 30 min, and obtain pre-emulsion B; S3: In a reaction kettle equipped with a stirrer, add 0.8 g of sodium bicarbonate, 40 g of softened water, and 50 g of pre-emulsion A, heat to 80°C, add 1 g of potassium persulfate, react for 0.5 h, slowly add the remaining pre-emulsion A and 0.8 g of potassium persulfate, keep warm for 1 h, slowly add pre-emulsion B and 1.2 g of potassium persulfate, keep warm for 3 h, and obtain a mixed emulsion; S4: Cool down with circulating water, repeat 3 times, adjust the pH to 8, let it stand for 1 hour, and then dry.

[0039] Performance testing Detection Methods 1. Rheological properties test method The capillary rheometer was used to measure the change of melt viscosity with shear rate. The test temperature was set at 210°C. Generally, the smaller the shear viscosity, the better the fluidity. The test results are as follows: Figure 1 shown.

[0040] 2. Melt flow rate test method According to the standard GB / T3682-2000, the melt flow rate was measured using a melt flow rate meter at a temperature of 230°C and a load of 2.16 kg. The larger the melt flow rate value, the better the fluidity. The results are as follows: Figure 2 shown.

[0041] 3. Mechanical properties test method Referring to the standard GB / T1043-1993, the impact performance was measured using a pendulum impact tester. The specimens were placed at -20°C for 6 hours before testing. Referring to the standard GB / T1040-1992, the tensile performance was measured using a universal material testing machine. The test results are as follows: Figure 3 shown.

[0042] Results Analysis from Figure 1 It can be seen that with the increase of shear rate, the viscosity of acrylate copolymer decreases. At the same shear rate, after hydroxy acrylate modification or polysiloxane modification, the melt viscosity decreases and the fluidity becomes better.

[0043] from Figure 2 It can be seen that the melt flow rate of the high-melt and high-fluidity acrylate copolymer obtained by the example is larger than that of the comparative example, indicating that the modification of hydroxy acrylate and the introduction of organosiloxane are both beneficial to improving the melt fluidity.

[0044] from Figure 3 It can be seen that the modification of hydroxy acrylate and the introduction of polysiloxane are beneficial to improving the impact strength of acrylate copolymer at low temperature, thereby improving its toughness; in addition, the modification of acrylate copolymer by nonionic surfactant is also helpful to improve its tensile strength and impact strength.

[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-melt high-fluidity acrylic copolymer, characterized in that: The steps include: S1: Mixing softened water and an emulsifier, stirring, heating and emulsifying to obtain an emulsified solution; S2: reacting hydroxy acrylate, stearic acid and catalyst at 130-160°C for 3-5h, cooling to 60-80°C after the reaction, washing and vacuum drying the product to obtain modified hydroxy acrylate; S3: mixing and stirring the emulsified solution and the modified hydroxy acrylate to obtain a pre-emulsion A; mixing and stirring the emulsified solution, methyl methacrylate, styrene and a silane coupling agent to obtain a pre-emulsion B; S4: Sodium bicarbonate, softened water and pre-emulsion A are stirred evenly, heated to 80°C, an initiator is added, and after reacting for 0.5-1h, pre-emulsion A and the initiator are slowly added, and the mixture is kept warm for 1-3h, pre-emulsion B and the initiator are slowly added, and the mixture is kept warm for 1-3h to obtain a mixed emulsion; S5: Cool down with circulating water, adjust the pH to 8-9, let stand and dry.

2. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 1, characterized in that: The mixed emulsion in step S4 is modified by a method comprising the following steps: In the organosiloxane solution, add hydrochloric acid dropwise while stirring, adjust the solution pH to 4-5, react for 3-5 hours, add emulsifier, acrylate monomer and mixed emulsion, stir evenly, heat to 75-85°C, slowly add initiator, adjust the pH to 8-9, and keep warm for 1-3 hours.

3. The method for preparing a high-melt high-fluidity acrylic copolymer according to any one of claims 1 to 2, characterized in that: The emulsifier is one or more of fatty alcohol polyoxyethylene ether sodium sulfate, nonylphenol polyoxyethylene ether and sodium dodecyl sulfate.

4. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 1, characterized in that: In step S2, the hydroxyacrylate is one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate; the catalyst is one of nano-silicon dioxide, nano-alumina and nano-zirconium oxide; the mass ratio of the hydroxyacrylate, stearic acid and catalyst is 100: (100-250): (0.8-2.4).

5. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 1, characterized in that: In step S3, the silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane; the mass ratio of the modified hydroxy acrylate, methyl methacrylate, styrene and silane coupling agent is 100: (100-200): (50-80): (5-10).

6. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 1, characterized in that: In step S4, the initiator is potassium persulfate or ammonium persulfate; the ratio of the total mass of the pre-emulsion A and the pre-emulsion B to the total mass of the initiator used is 100:(1.2-2.5).

7. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 2, characterized in that: The organosiloxane is one or more of methyltrimethoxysilane, methyltriethoxysilane and hexamethyldisiloxane; the mass fraction of the organosiloxane solution is 20%.

8. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 2, characterized in that: The mass ratio of the acrylic ester monomer, the organic siloxane, the mixed emulsion and the initiator is 1:(5-10):(10-30):(0.01-0.03).

9. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 2, characterized in that: The obtained high melt high fluidity acrylic ester copolymer is modified by a method comprising the following steps: Dissolve the nonionic surfactant in toluene to prepare a solution with a mass fraction of 1%-5%, add the high-melt high-fluidity acrylic copolymer, swell for 5-15 minutes, take out, wash and vacuum dry.

10. The method for preparing a high-melt high-fluidity acrylic copolymer according to claim 9, characterized in that: The nonionic surfactant is one or more of Poloxamer F188, Poloxamer F127 and Poloxamer F68.

Citation Information

Patent Citations

  • Synthesis method of organic silicon modified acrylate copolymer

    CN102464784A

  • Real stone paint emulsion and preparation method thereof

    CN112940170A

  • Emulsion for novel environment-friendly water-based antirust coating and preparation method thereof

    CN116751342A

  • Aqueous emulsion polymers as rheology modifiers, compositions thereof, and method of use

    US20190040172A1